2010
DOI: 10.1590/s1413-70542010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Brachiaria humidicola (Rendle) Schweick em diferentes idades de rebrota submetida a doses de nitrogênio e potássio

Abstract: Avaliou-se o efeito da aplicação de doses de nitrogênio associado ao potássio, em quatro idades de rebrota, sobre o índice de área foliar (IAF), produção de matéria seca (MS), teores de proteína bruta (PB) e fibra em detergente neutro (FDN) e relação folha/colmo (F/C) de Brachiaria humidicola (Rendle) Schweick. Foram testadas as seguintes doses de nitrogênio (N), na forma de uréia agrícola, e de potássio (K2O), na forma de cloreto de K, em kg/ha/ano: 0 de N + 100 de K2O; 100 de N + 100 de K2O; 200 de N + 200 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Costa et al (2007) found that the recommended date to forage regrowth was between 28 and 42 days for Brachiaria brizantha cultivar Marandu and between 28 and 35 days for BRA-004308 and BRA-003395 genotypes. However, Deminicis, Abreu, Vieira, and Araújo (2010) reported that 56 regrowth days resulted in higher yield for Brachiaria humidicola. However, those works disregarded the structural evaluations of tissues, which may show declines in digestibility with increasing age.…”
Section: Resultsmentioning
confidence: 98%
“…Costa et al (2007) found that the recommended date to forage regrowth was between 28 and 42 days for Brachiaria brizantha cultivar Marandu and between 28 and 35 days for BRA-004308 and BRA-003395 genotypes. However, Deminicis, Abreu, Vieira, and Araújo (2010) reported that 56 regrowth days resulted in higher yield for Brachiaria humidicola. However, those works disregarded the structural evaluations of tissues, which may show declines in digestibility with increasing age.…”
Section: Resultsmentioning
confidence: 98%
“…Ademais, cabe ressaltar que o resultado encontrado neste trabalho é em produção de proteína bruta por área. A resposta em concentração de proteína bruta à adubação nitrogenada é menos evidente que a de produção de matéria seca (Mesquita, Neres, 2008;Deminicis et al, 2010), pois esse aspecto sofre maior limitação da variabilidade genética, uma vez que a herdabilidade da primeira pode variar entre 0,66 e 0,74 (Vogel et al, 1981;Figueiredo et al, 2012) e a da segunda está entre 0,47 e 0,57 (Jiang et al, 2014;Mateus et al, 2015;Simeão et al, 2016).…”
Section: Resultsunclassified
“…However, Alexandergrass exhibited lower DM content compared with the other treatments, which can potentially be explained by its higher leaf:stem ratio, which results in lower concentrations of dry material (Deminicis et al, 2010). Moreover, annual plants, such as Alexandergrass, accumulate less senescent material, unlike perennial species, which live for long periods in the soil.…”
Section: Discussionmentioning
confidence: 97%